FUNGSI PENGAWASAN BADAN PERMUSYAWARATAN DESA DALAM PENYERAPAN ANGGARAN PENDAPATAN DAN BELANJA DESA MENURUT UU NO. 6 TAHUN 2014(STUDI KASUS DI DESA RIANG GEDE KECAMATAN PENEBEL KABUPATEN TABANAN) - Devi, Ni Putu Chyntia Sandrina; Erviantono, Tedi; Supriliyani, Ni Wayan (CITIZEN CHARTER, 2016)
ABSTRACT Village Consultative Body (BPD) is a village-level institutions which carry out the functions of government. The Law No. 6 of 2014 on the village at this time strengthens the function of Village Consultative Body (BPD) is the supervisory function mainly supervisory function BPD conducted on the absorption Budget Village (APBDes). The purpose of this study is to determine the supervisory function of BPD in the absorption APBDes by referring to the Law No. 6 of 2014 by using the steps in the regulatory process, namely (1) the establishment of standards, (2) the determination of the measurement of the activities, (3) measurement of the activities, (4) comparing the implementation of standards and analysis of deviations and (5) taking corrective action when needed as well as the principles of good governance: accountability, transparency and participation. This type of research used is descriptive qualitative. Data collection techniques used in this study is the technique of interview, observation and documentation study. The results of this study indicate that the monitoring function BPD based on stages in the regulatory process has been implemented, but could not be implemented to the fullest by BPD Riang Gede because BPD could not be close to the village community. When viewed from the principles of good governance in the absorption APBDes in Desa Riang Gede could not be implemented to the maximal by the village government for accountability, transparency and participation have not been able to reach all the village community. Other obstacles that cause BPD Riang Gede has not been able to implement good performance due to the busy activities of BPD members who have other jobs besides carrying out oversight functions APBDes. Besides the lack of operational funds for BPD members in carrying out its performance also affects the performance of BPD. Keywords: Supervisory Function, Village Consultative Body, Absorption Village Budget